Effect of Basic Sites over Zirconium-based Catalysts on the Catalytic Performance of Higher Alcohols Synthesis from Syngas - Ge ZHANG; Linshu LI; Wei HUANG (Taiyuan Ligong Daxue xuebao, 2023)
Synthesis of higher alcohols from syngas involves two important issues in C1 chemistry, the retention and breaking of C—O bond, in which the basic sites has been shown to be beneficial to inhibiting hydrocarbon generation. In this paper, monoclinic zirconia (m-ZrO2) and tetragonal zirconia (t-ZrO2) with different basic quantity and basic strength were prepared by hydrothermal method and precipitation method, respectively, and the corresponding catalysts Cu/m-ZrO2 and Cu/t-ZrO2 were prepared by impregnation method. The effect of basic sites over these catalysts on the catalytic performance of higher alcohols synthesis from syngas was investigated. XRD, N2 desorption, H2 temperature programmed reduction (H2-TPR), FT-IR, and CO2 temperature programmed desorption (CO2-TPD) were used to discuss the structural-activity relationship of the catalysts. The results show that the medium and strong basic sites on the catalysts are beneficial to the improvement of total alcohol yield. Monoclinic ZrO2 (m-ZrO2) and its catalyst (Cu/m-ZrO2) possess a high surface total alkali quantity, a high proportion of weak basic sites, and a high concentration of hydroxyl groups related to weak base sites, which is considered to be conducive to methanol production. Tetragonal ZrO2 (t-ZrO2) and its catalyst (Cu/t-ZrO2) possess a high proportion and density of medium and strong basic sites, and a high O2- concentration, which is considered to be conducive to C2+ alcohol formation. The relationship between the properties, quantity, and strength of base sites on the catalysts and the distribution of alcohols was clarified.